Quantum error correction and local topological order from Quantum Double model (2025)
This thesis presents a detailed analysis of the quantum double model and its twisted version, focusing on their properties as quantum error-correcting codes. In the case of Kitaev's quantum double model for finite Abelian groups, the error correction process is explicitly described. The number of correctable errors depends on the lattice and the topology of the underlying surface. Although there exists a theoretical maximum number of errors that can be corrected, it is proven that correcting this number of errors is, in general, an NP-complete problem. As an alternative, a polynomial-time correction algorithm is proposed that corrects a number of errors below the theoretical maximum. In regard to the twisted quantum double model, it is studied within the framework of Local Topological Order (LTO). Originally formulated for square lattices, the definition of LTO is extended here to arbitrary two-dimensional lattices, enabling an explicit characterization of the ground states space through invariant spaces of monomial representations. By reformulating the LTO conditions to include such general lattices, it is proven that the twisted model satisfies all four axioms of LTO on any 2D lattice. As a result, the ground states space of the model is shown to define a quantum error-correcting code, highlighting the role of topological order in fault-tolerant quantum computation.